Konseling Keluarga dengan Terapi Regulasi Emosi dan Terapi Bermain untuk Menurunkan Internet Addiction pada Anak-Anak (Jurusan Bimbingan dan Konseling Islam, 2022)
This study aims to determine the effect of emotional regulation therapy and play therapy on reducing internet addiction in children. The subjects in this study were 14 children who experienced internet addiction with their mothers. The hypothesis proposed in this study is that there is a difference between internet addiction in children who follow emotion regulation therapy and play therapy with children with internet addiction who do not follow emotion regulation therapy and play therapy. The research design used is the control group design. Quantitative analysis used an independent sample t-test to determine whether or not there was an effect of emotion regulation therapy and play therapy on reducing internet addiction in the experimental group given emotion regulation therapies and play therapy with the control group not receiving emotion regulation therapy and play therapy. . The results of the study, in the form of all aspects of internet addiction, showed a very significant difference, children with internet addiction in the control group and the experimental group were given treatment with a final internet addiction test score with a value of p = 0.007 (P < 0.01).